Ordered Carbon Nanotubes and Globular Opals As a Model of Multiscaling Photonic Crystals - Dovbeshko, G.; Fesenko, O.; Moiseyenko, V.; Gorelik, V.; Boyko, V.; Sobolev, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Experimental data on carbon nanotube carpet and synthetic opals have been
compared by visible, infrared spectroscopy, and electron microscopy. Spectral features of
the objects under study in infrared region are registered. Three regions of abnormal
behavior of reflectance and absorbance for carbon nanotube carpet and two regions for
opals in the 7000-2000 cm⁻¹ are observed in comparison with the separated nanotubes or
SiO₂ globules in disordered states and/or condensed state. The spectroscopic features of
the photonic crystals caused by their different microstructures at different length scales
and basis for development of a proper model for light propagation through the photonic
crystals in the IR region are presented for discussion.